Measurement of local oil holdup for oil-in-water emulsion flows using multiple mini-conductance probes. (June 2018) - Han, Y.F.; Jin, N.D.; Ren, Y.Y.; Han, T.H.; Huang, Z.H.
Highlights: We design multiple mini-conductance probes for measuring local oil holdup in oil-water emulsions. We implement an experiment of pipeline flow of emulsions with low velocity and high water-cut. We extract and compare oil holdup distributions on different positions at the pipe cross section. We investigate the complexity in the motion of oil droplets using weighted-permutation entropy. Abstract: In the present work, local oil holdup in oil-in-water emulsion flows is experimentally investigated with multiple mini-conductance probes. With the aid of finite element method (FEM), we firstly optimize the geometry structure of a mono-sensor conductance probe through the examination on its electrical and sensitivity field distribution. Thereafter, multiple mini-conductance probes composed by 16 mono-sensor probes are designed for a vertical upward pipe with 20 mm inner diameter (ID). The flow conditions regarding pipeline flows of oil-in-water emulsion are set within low velocity (0.0184–0.2576 m/s) and high water-cut (80–96%). By processing the fluctuating signals of multiple mini-conductance probes, we derive oil holdups on different positions at pipe cross section. Accordingly, oil holdup distribution at the whole pipe cross section is acquired using cubic spline interpolation, and correspondingly the slippage effect between oil and water phase is analyzed. The research results indicate that local oil holdup distribution is susceptible to the variation in mixture velocity and water-cut. Furthermore, the degree of inhomogeneous distribution in local oil holdup presents the weakest under the conditions of high mixture velocities as well as high water-cuts. Finally, a complexity measure designated as weighted-permutation entropy is extracted from the fluctuating signals of multiple mini-conductance probes to characterize the evolution in oil holdup distribution from the perspective of nonlinear dynamics.